Prevalence of Bullying and Cyberbullying in the Last Stage of Primary Education in the Basque Country - Machimbarrena, Juan Manuel; Garaigordobil, Maite (Spanish Journal of Psychology, 2019)
Bullying and cyberbullying pose a serious problem in our schools. Despite this research area's increasing relevance, most research into cyberbullying in the present day has focused only on adolescents. However, given the long-lasting effects of victimization, it is necessary to understand its prevalence throughout the different educational stages of students. This study aims to clarify the prevalence of bullying and cyberbullying among students in the 5(th) and 6(th) grades. A sample of 1,993 (M-age = 10.68, SD = 0.71; range 9-13) students completed the Cyberbullying: Screening of Peer-Harassment test. The results reveal that 20.3% (n = 404) were pure victims, 6.1% (n = 121) pure bullies, 23.9% (n = 476) bully-victims, and 28.9% (n = 575) pure bystanders of bullying. With respect to cyberbullying, 13.4% (n = 267) were pure cybervictims, 0.7% (n = 13) pure cyberbullies, 3.1% cyberbully-victims (n = 62), and 25.6% (n = 510) pure cyberbystanders. In addition, the results reveal that verbal aggression and offensive or insulting messages were the most prevalent forms of aggression in bullying and cyberbullying, respectively. 36.6% of the sample had suffered verbal aggression and 8.4% had received offending or insulting messages. These data show that bullying and cyberbullying are considerably prevalent in this educational stage.
Keywords: bullying; children; cyberbullying; prevalence; JCR; Scopus